Health benefits of hard martial arts in adults: a systematic review. Issue 14 (18th July 2018) - Origua Rios, Sandra; Marks, Jennifer; Estevan, Isaac; Barnett, Lisa M.
ABSTRACT: Participation in organized sports is promoted as a means of increasing physical activity levels and reducing chronic disease risk in adults. Hard martial arts practice (i.e. using body contact techniques), has gained in popularity over time. This review explores the evidence for health benefits of "hard" martial arts practice within the adult population. A systematic electronic database search was conducted, and quality assessments applied the Effective Public Health Practice Project tool. Twenty-eight studies met the inclusion criteria, examining balance, cognitive function, muscular skeletal status, psychological, cardiovascular fitness, and metabolic effects. The majority of studies reported positive effects resulting from hard martial arts practice, showing some improvement and maintenance of balance, cognitive function and psychological health. Benefits may be obtained regardless of the age of practice commencement. However, quality of the evidence is affected by methodological weaknesses across the studies. "Hard" martial arts seem to have potential to improve balance and cognitive functions that decline with age, which can lead to poorer health outcomes among the elderly (e.g. cognitive decline, falls and fractures). Benefits should be further investigated with improved intervention studies, representative samples and longer follow-up periods in order to establish associations with morbidity and mortality in the long term.